Correlation of Nutritional Status and Sleep Quality With Incidence Primary Dysmenorrhoea in Obstetric Students - Anita Yuliani; Rahmat Rahmat; Rosa Hasti Ayu Oktavia; Diana Papila (Politeknik Kesehatan Kemenkes Mamuju, 2023)
Women in worldwide had experienced dysmenorrhea, with 10-15% experiencing severe dysmenorrhea. The intensity and pain can affect sleep quality. Out of 51 female undergraduate midwifery students, 20 of them experienced dysmenorrhea. They reported having difficulty sleeping and often slept after 11 PM. During lectures, some of them felt exhausted. This study aimed to identify the correlation between nutritional status and sleep quality with the occurrence of primary dysmenorrhea in midwifery students. This research was a quantitative study with an analytic cross-sectional design. The sample consisted of 107 undergraduate midwifery students selected using a total sampling technique. Data collection involved measuring the weight and height of respondents to categorize their body mass index (BMI), and then the respondents completed the Pittsburgh Sleep Quality Index (PSQI) questionnaire and the Numeric Rating Scale (NRS) questionnaire for primary dysmenorrhea. Data analysis was conducted using the Spearman rank correlation test. The results showed a significant negative correlation between nutritional status and the occurrence of dysmenorrhea, as well as a meaningful correlation between sleep quality and primary dysmenorrhea in midwifery students. Based on this research, we concluded that there was a correlation between nutritional status and sleep quality with the occurrence of primary dysmenorrhea.